A fluorine-modified photoresist, a preparation method thereof and a preparation method of a Nano-LED device
Patent Information
- Application Number
- CN202611415866.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]尽管上述技术路线各有优势,但在“直接面向器件集成的氟改性模板层”与“可计算/可设计的选择性填充判据”层面仍存在空白:特别是在模板上表面为低表面能含氟层、下表面为较高表面能功能层的情况下,孔口处 的表面能差异会加剧三相线钉扎,诱发孔口桥连,降低填充成功率并引入像素缺陷;同时,孔间残留难以持续、可控地降低,从而限制了对光学色串扰的抑制与图像对比度提升
本发明提供的氟改性(甲基)丙烯酸烷基酯带有全氟侧链的单体,由于该全氟侧链具有向表面自发迁移的倾向,可在固化后于模板表面形成富氟层,从而降低模板表面能,并建立有利于退浸润的表面能梯度。
Smart Images

Figure CN122923352A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor optoelectronic device technology, specifically relating to a fluorine-modified photoresist and its preparation method, and a method for preparing Nano-LED devices. Background Technology
[0002] For next-generation information terminals targeting near-eye displays such as augmented reality / virtual reality (AR / VR), display device sizes are evolving from "micrometer-scale panel displays" to "nanometer-scale pixels approaching optical limits." To achieve ultra-high pixel density full-color displays, sub-pixel sizes need to be further reduced to sub-micrometer or even nanometer scales.
[0003] Colloidal quantum dots (QDs) are considered important candidate luminescent materials for realizing high PPI microdisplays due to their advantages such as tunable emission wavelength, narrow spectral half-width, high color purity, and solution-processability. However, in nanoscale pixelation, quantum dot solution deposition is often limited by problems such as the "coffee ring effect," leakage and optical crosstalk caused by interpore residues, and the dissolution / damage of the charge carrier transport layer by patterning processes.
[0004] In existing technologies, during spin coating or inkjet deposition of quantum dot luminescent layers, solvent evaporation-induced edge pinning and lateral flow easily cause uneven film thickness / composition. Conventional photoresists and developing systems (alkaline aqueous solutions or polar organic solvents) easily dissolve or erode organic hole injection / transport layers such as PEDOT:PSS, TFB, and PF8Cz, leading to device interface degradation. To address the patterning problem, Chinese patent application CN105098002A discloses quantum dot patterning through photoresist patterning, hydrophilic treatment, and stripping, or Chinese patent application CN112051709A discloses the preparation of quantum dot photoresist by mixing quantum dots with photoresist mother liquor. However, the above solutions still struggle to simultaneously achieve at the nanoscale: gentle processing of the organic layer in an orthogonal manner, selective and uniform filling of the pores, and effective suppression of inter-pore residues.
[0005] In academia, recent years have seen Nature journals report strategies for fabricating ultra-high resolution nano-LEDs based on nanopore array molds and utilizing capillary self-assembly, demonstrating the potential of "capillary confined self-assembly" in ultra-high PPI self-emissive displays. Nature has also reported on achieving high-fidelity quantum dot patterns >10,000 PPI using template-assisted dielectrophoresis and other methods. Science Advances and other journals have also reported high-yield assembly of quantum dot arrays using DNA / surface-assisted templates, further supporting the scalability of the "template + self-assembly" approach.
[0006] Despite the advantages of each of the above technical approaches, gaps remain in the areas of "fluorine-modified template layers directly oriented towards device integration" and "calculable / designable selective filling criteria." In particular, when the upper surface of the template is a low surface energy fluorine-containing layer and the lower surface is a high surface energy functional layer, the surface energy difference at the aperture will exacerbate three-phase line pinning, induce aperture bridging, reduce the filling success rate, and introduce pixel defects. At the same time, the residue between apertures is difficult to reduce continuously and controllably, thus limiting the suppression of optical color crosstalk and the improvement of image contrast. Summary of the Invention
[0007] To address the aforementioned issues, this invention provides a fluorine-modified photoresist capable of achieving "orthogonal patterning" of fluorine modification on an organic carrier transport layer. This invention also provides a method for fabricating Nano-LED devices based on a selective filling criterion using aperture tilt design: by introducing an additional aperture tilt angle / funnel-shaped geometry at the aperture inlet of the fluorine-modified template, the inlet capillary pressure is ensured to be positive, thereby effectively driving luminescent materials such as quantum dots to selectively enter the template apertures. Simultaneously, during the spin-coating and dewetting process, inter-aperture residues are continuously removed, suppressing optical crosstalk and obtaining high-contrast PL images.
[0008] This invention provides a fluorine-modified photoresist, the contents of which are as follows: 40–50 wt% phenolic epoxy acrylate Polydipentaerythritol pentaacrylate 10–20 wt% Fluorine-modified alkyl (meth)acrylate 5-15 wt% Photoresist solvent 15-35 wt% Free radical initiator 0.5-2 wt%; Two-photon sensitizer 20–150 μM; Triethylamine 0.1–1 wt% Anti-self-polymerizing agent 50–200 ppm.
[0009] This invention regulates the content of fluorinated (meth)acrylate alkyl esters to adjust the monomers with perfluorinated side chains, thereby changing the fluorine-rich level on the template surface after photoresist curing. This allows for continuous control of the template surface energy, contact angle, and dewetting behavior. If the content is too low, the template surface cannot form suitable surface energy and contact angle after photoresist curing, thus preventing dewetting behavior. If the content is too high, the surface energy of the colloidal film becomes too low, resulting in surface energy mismatch during spin coating and making stable photolithography impossible.
[0010] The phenolic epoxy acrylate provided by this invention serves as both the main resin and the crosslinking framework. On one hand, it increases the system viscosity, thereby inhibiting dewetting of the photoresist film during film formation and subsequent processing. On the other hand, it provides the necessary mechanical strength, swelling resistance, and structural stability for the template layer after exposure and curing. Furthermore, the multifunctional PETA monomer, with its polyacrylate branches, can further enhance the free radical polymerization rate and curing depth, facilitating rapid and deep curing.
[0011] The mixed solvent system provided by this invention (such as PGME / PGMEA and GBL, or a combination of HFE, cyclopentanone, and GBL) is used to adjust the saturated vapor pressure, evaporation rate, and solubility parameters, reduce undesirable photoresist residues on the HTL surface, and balance film quality with compatibility with the underlying organic layer.
[0012] This invention uses phenolic epoxy acrylate as the main crosslinking backbone, introduces fluorinated alkyl (meth) acrylate as a diluent monomer, and employs free radical initiators such as TPO-L / BAPO / DETC in conjunction with coumarin / eosin two-photon sensitizers to achieve 405 nm single-photon exposure or 515 / 780 nm two-photon polymerization exposure; by using triethylamine to synergistically initiate and inhibit oxygen inhibition polymerization, curing can also be completed in an air environment.
[0013] Preferably, the fluorinated alkyl acrylate is: perfluoropolyether methacrylate (PFPE-MAA), hexafluorobutyl methacrylate, or tridecylfluorooctyl methacrylate.
[0014] Preferably, the photoresist solvent includes one or more of hydrofluoroether, cyclopentanone, and γ-butyrolactone solvents.
[0015] More preferably, the hydrofluoroether is one or more of HFE-7100, HFE-7200, and HFE-7300.
[0016] Preferably, the free radical initiator is one or more of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (TPO-L), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (BAPO), and 2,4-diethylthiazolidinone (DETC).
[0017] Preferably, the two-photon sensitizer is one or more of coumarin-102, 7-diethylamino-4-methylcoumarin, and eosin Y.
[0018] Preferably, the anti-self-polymerization agent is p-hydroxyanisole or 2,6-di-tert-butyl-p-cresol.
[0019] Preferably, the amount of triethylamine used is 0.3–0.5 wt% to inhibit oxygen inhibition and improve the curing rate in an air environment.
[0020] On the other hand, the present invention also provides a method for preparing the fluorine-modified photoresist, comprising: (1) Prepare the ingredients according to the content of each component of the fluorine-modified photoresist, and then add phenolic epoxy acrylate, polydipentaerythritol pentaacrylate and fluorine-modified alkyl acrylate to the photoresist solvent and stir to obtain a mixed solution. (2) Add free radical initiator and two-photon sensitizer to the mixed solution until completely dissolved, then add triethylamine and anti-self-polymerization agent, and then vacuum degas and filter to obtain fluorine-modified photoresist.
[0021] Preferably, in step (1), the mixture is stirred at 30-40°C for 30-40 minutes.
[0022] Preferably, in step (2), the fluorine-modified photoresist is obtained by filtration through a polytetrafluoroethylene (PTFE) filter membrane.
[0023] More preferably, the PTFE filter membrane has a pore size of 0.22–0.35 μm.
[0024] Preferably, the obtained fluorine-modified photoresist is stored in a light-protected environment at 4-8°C.
[0025] Preferably, the surface energy of the fluorinated template layer obtained after curing the fluorinated photoresist is less than 30 mN / m, and the water contact angle is greater than 100°. This invention provides a fluorinated template layer obtained after curing the fluorinated photoresist that exhibits resistance to swelling by octane, toluene, or hydrofluoroether developers.
[0026] On the other hand, the present invention also provides a method for fabricating a Nano-LED device, comprising: (1) A first carrier transport layer is formed on the bottom electrode; (2) A patterned fluorine-modified template layer is obtained by spin-coating the photoresist onto the first carrier transport layer, followed by exposure and development. The patterned fluorine-modified template layer contains an array of nanopores. The inlet of each nanopore has a tapered flared structure, and the capillary pressure ΔP at the inlet of each nanopore is... entry = 2γ·cos(θ eff ) / r entry , θ eff = θ F – α, and ΔP entry > 0, γ is the surface tension of the filling liquid, r entry The equivalent radius of the hole inlet is equal to the actual top hole diameter (r) after the template holes are superimposed at the angle obtained from the exposure. entry=d+h*tanα), where d is the inner diameter of the hole, h is the height of the conical hole-enlarging structure, and θ eff To account for the effective contact angle after considering the additional hole inclination angle, θ F The intrinsic contact angle is α, where α is the angle of inclination of the pore axis of the nanopore relative to the normal of the template pore. (3) Add or spin-coat a luminescent material solution to the patterned fluorine-modified template layer, so that the luminescent material selectively fills into the nanopores under the drive of the inlet capillary pressure, and removes the residue between the pores during the spin-coating dewetting process to obtain a nano luminescent layer; (4) A second carrier transport layer and a top electrode are sequentially deposited on the nano-light-emitting layer and then encapsulated to obtain a Nano-LED device.
[0027] The selective filling criterion and orifice tilt angle design mechanism provided by the present invention are as follows: (1) Inlet capillary pressure criterion: for an inlet equivalent radius of r entry For the template hole, the inlet capillary pressure of the filling liquid can be approximately expressed as: ΔP entry = 2γ·cos(θ eff ) / r entry Only when ΔP entry > 0 (i.e., θ) eff When < 90°, capillary pressure can drive the filling liquid into the pore and carry QDs and other nanoparticles to achieve pore filling. (2) Pore bridging problem: When the upper surface of the template is a fluorine-containing low surface energy layer (liquid-repellent to non-polar solvents, θ F When the angle is often greater than 90°, and the bottom / lower surface of the hole is a functional layer (high surface energy, small contact angle), three-phase line pinning and liquid bridge / bridging are likely to occur at the orifice, which will hinder the filling front from entering the hole, resulting in voids or uneven filling in the hole. (3) Introduction of additional tilt angle / funnel inlet: In order to overcome θ F To address the "non-wetting" state caused by a 90° angle, this invention introduces an additional hole inclination angle α (the inclination of the hole axis relative to the template hole normal) at the hole inlet, ensuring that the effective contact angle satisfies θ. eff = θ F - α. When θ is satisfied F < 90° + α, which makes θ eff < 90°, therefore ΔP entry > 0, the in-hole filling is effectively driven and the probability of hole bridging can be significantly reduced. 3D machining realization: Two-photon lithography (TPL) can be used to directly write 3D hole structures with controllable α (such as tilted cylindrical holes, conical holes, flared holes or "wider at the top and narrower at the bottom" converging holes) into the template layer, realizing arbitrary adjustment of the hole tilt angle.
[0028] Preferably, the luminescent material is at least one of colloidal quantum dots, perovskite luminescent materials, organic luminescent materials, or polymer luminescent materials.
[0029] More preferably, the perovskite luminescent material is a perovskite quantum dot or a perovskite precursor solution.
[0030] This enables the fabrication of universal nanoscale luminescent pixels; and through the selective filling and dewetting removal process, the residual luminescent material between holes is significantly reduced, thereby suppressing optical color crosstalk and obtaining high-contrast photoluminescence (PL) images.
[0031] Preferably, the semi-cone angle φ is 8°-12°. This invention further controls the semi-cone angle of the conical flared structure, ensuring that the effective contact angle, considering the additional hole inclination angle, is within the optimal range. Combined with the fluorinated monomer ratio to form a fluorine-rich layer, the luminescent material solution can stably enter the template holes during spin coating, forming a tight, uniform filling without obvious voids. Simultaneously, there is virtually no residue or only very little residue between holes, thereby obtaining a high-contrast PL image and significantly reducing optical crosstalk between pixels. The quantum dots fill the holes uniformly and tightly, with stronger selectivity (i.e., no excessive residue between holes).
[0032] Preferably, the pixel aperture of the array formed by multiple nanopores is 300-500 nm and the pixel period is 600-1000 nm; more preferably, the pixel aperture is 300 nm and the pixel period is 600 nm, corresponding to a pixel density of 25,400-42,333 PPI.
[0033] Preferably, the bottom electrode is made of indium tin oxide (ITO) or indium gallium zinc oxide (IGZO), and the top electrode is made of gold (Au), silver (Ag), or aluminum (Al).
[0034] Preferably, the first carrier transport layer is a hole injection layer and / or a hole transport layer.
[0035] Preferably, the second carrier transport layer is an electron transport layer.
[0036] Compared with the prior art, the beneficial effects of the present invention are as follows: The fluorinated (meth)acrylate monomer provided by this invention has a perfluorinated side chain. Since the perfluorinated side chain has a tendency to spontaneously migrate to the surface, it can form a fluorine-rich layer on the template surface after curing, thereby reducing the template surface energy and establishing a surface energy gradient that is conducive to dewetting.
[0037] This invention achieves "equivalent wettability" on the conical flared structure of the fluorine-containing surface with θ_F > 90° by adjusting the inclination angle α of the nanopore axis relative to the template hole normal. This allows the luminescent material solution between the nanopores to selectively slide into the nanopores under the action of capillary force through the conical flared structure, and the luminescent material solution inside the nanopores is not easy to escape. At the same time, the residue between the pores is continuously removed during the spin coating and dewetting process, which suppresses optical color crosstalk and obtains a high-contrast PL image. Attached Figure Description
[0038] Figure 1 The preparation process of the photoresist solution provided in Embodiment 1 of the present invention; Figure 2 Optical microscope and atomic force microscope (AFM) images of a photoresist solution spin-coated silicon wafer provided in Embodiment 1 of the present invention; Figure 3 These are contact angle images of the photoresist-cured film surface provided in Embodiments 1, 2, and 2 of the present invention, wherein... Figure 3 Image (a) in Example 1 shows the contact angle of the film surface after the photoresist has cured. Figure 3 Image (b) in Example 2 shows the contact angle of the film surface after the photoresist has cured. Figure 3 (c) in Comparative Example 2 shows the contact angle image of the film surface after photoresist curing; Figure 4 The diagram shows the mechanism of photoresist, AFM images of etching and filling the nano-light-emitting layer, and nanopore size diagram provided in Embodiment 3 and Comparative Example 2 of the present invention. Figure 5 The contrast PL images of fluorine-modified photoresist and ordinary photoresist etching and filling of nano-luminescent layers are provided in Embodiment 3 of the present invention; Figure 6 The AFM images, nanopore size diagrams, and contrast PL images of the fluorine-modified photoresist etching and filling of the nano-luminescent layer provided in Embodiment 3 of the present invention; Figure 7 The AFM images, nanopore size maps, and contrast PL images of the fluorine-modified photoresist etching and filling of the nano-luminescent layer provided in Embodiment 4 of the present invention; Figure 8 This is a flowchart of the fabrication of a Nano-QLED device provided in Embodiment 5 of the present invention; Figure 9 Microscopic images of the Nano-QLED template hole and electroluminescence (EL) micrographs of the Nano-QLED obtained in Example 5 of this invention; Figure 10The diagram and micrograph show the electroluminescence (PL) structure of the perovskite luminescent material prepared in Example 6 of this invention. Detailed Implementation
[0039] The technical solution of the present invention will be further described below with reference to embodiments. It should be noted that the following embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.
[0040] Example 1 Weigh 4.5 g of phenolic epoxy acrylate, 1.9 g of DPEPA, 0.1 g of PFPE-MAA, and 3 g of cyclopentanone into a dry flask and stir at 35°C for 30 min to obtain a clear mixed solution. Then add 0.1 g of BAPO and continue stirring until completely dissolved. Next, add 0.05 g of triethylamine (TEA) and 0.001 g of the anti-self-polymerization agent BHT. After sonicating for 3 min to remove bubbles, filter through a 0.22 μm PTFE membrane to obtain a transparent fluorine-modified photoresist. This photoresist can be spin-coated at 3000–5000 rpm to form a 30–60 nm film. The preparation process and the obtained photoresist solution are as follows. Figure 1 As shown.
[0041] Subsequently, spin coating and 405 nm UV exposure (or 515 / 780 nm two-photon exposure) are performed on the silicon wafer to form large-area 500 nm aperture array structures for optical and atomic force microscopy (AFM) images, as shown below. Figure 2 As shown.
[0042] In the photoresist solution prepared in Example 1, the total amount of fluorinated monomers added was 1 wt%.
[0043] Example 2 Unlike Example 1, the mass of PFPE-MAA added was 0.05 g, resulting in an addition amount of 0.5 wt% of fluorinated monomer.
[0044] Comparative Example 1 Unlike Example 1, the mass of PFPE-MAA added was 0.2g, resulting in an addition of 2 wt% of fluorinated monomer (please provide the specific value and confirm the amount, which should correspond to the mass of PFDA added). This caused the surface energy of the colloidal film to be too low, leading to surface energy mismatch during spin coating and thus making it impossible to stably perform photolithography.
[0045] Comparative Example 2 Unlike Example 1, no PFPE-MAA was added, resulting in a fluorine content that was too low to form a suitable surface energy and contact angle on the photoresist-cured template surface, thus preventing the dewetting behavior from being achieved.
[0046] like Figure 3 As shown, octane droplets were dropped onto the surface of the cured photoresist film prepared in Examples 1-2 and Comparative Example 2, and the contact angle was measured. Figure 3 As shown in (a) of Example 1, when the amount of fluorinated monomer added is 1 wt%, the octane contact angle (CA) is 18.5°. Figure 3 As shown in (b) of Example 2, when the amount of fluorinated monomer added is 0.5 wt%, the octane contact angle (CA) is 14.5°. Further increasing the amount added easily leads to excessively low surface energy of the colloidal film, resulting in surface energy mismatch during spin coating and thus making stable photolithography impossible, as shown in Comparative Example 2. Figure 3 As shown in (c) of Comparative Example 2, the octane contact angle (CA) is 2.9° without the addition of fluorinated monomers.
[0047] Example 3 On a substrate with the anode (bottom electrode, indium tin oxide (ITO)) and hole transport layer (HTL, PF8Cz) prepared, the fluorine-modified photoresist prepared in Example 1 was spin-coated at 4000 rpm to form a film thickness of about 50 nm, and then soft-baked at 50–60 °C for 1 min.
[0048] Two-photon exposure patterning was performed using a 780 nm femtosecond laser source; after exposure, the area was placed in PGMEA developer for 20–60 s for development, the unexposed area was dissolved and removed, and the exposed area was cross-linked and cured to form a fluorine-modified template hole array with a diameter of about 500 nm; after development, the area was dried with nitrogen gas and then baked at 150 °C for 5–15 min to complete the cross-linking and curing.
[0049] An octane-dispersed CdSe / ZnS quantum dot solution (mass fraction 0.5–2.0 wt%, preferably 1.0 wt%) was dropwise added onto a fluorine-modified template pore array and spin-coated at 1000–3000 rpm for 20–60 s. During spin-coating, the quantum dot solution preferentially enters the pores under capillary pressure at the inlet. The interpore regions undergo dewetting due to the superhydrophobicity of the fluorine-modified surface, carrying away any residual quantum dots between the pores. This achieves selective filling of the nanoluminescent layer by "present in the pores / absent or very few between the pores".
[0050] The fabrication method on the fluorine-modified template hole array provided in Example 3 uses two-photon lithography (TPL) to directly write controllable α into the template layer, i.e. Figure 6 The three-dimensional aperture structure of θ1 (a converging aperture that is wider at the top and narrower at the bottom, where α = 10.8°) has r_entry of 157 nm, γ of 21.8 mN / m, and the calculated ΔP_entry is 2.74 * 10^- ... 8 Pa / m2 Achieving an ultra-high pixel density light-emitting array with a pixel aperture of 300 nm and a pixel period of 600 nm (approximately 42,333 PPI).
[0051] Atomic force microscopy (AFM) and photoresist imaging revealed that, compared to a conventional template using photoresist spin-coating as in Comparative Example 2, the quantum dot distribution within the holes in Example 3 was more uniform, and inter-hole residue was significantly reduced. This suppressed inter-pixel optical crosstalk and resulted in a high-contrast photoresist image. The mechanism of action is similar to that observed in AFM images. Figure 4 As shown, analysis of its height curve reveals that the bottom of the pixel hole is filled more evenly and densely, without a significant tapered drop. High-contrast PL images, as shown... Figure 5 As shown, the fluorescence intensity between pixels drops significantly, resulting in obvious contrast, while ordinary photoresist exhibits large areas of red fluorescence, making it impossible to distinguish pixel emission.
[0052] Example 4 The difference compared to Example 3 is the value of α, i.e. Figure 7 Given θ2 = 6.6° and diameter d = 500 nm, the calculated ΔP entry 1.5*10 8 Pa / m 2 .
[0053] like Figure 6 , Figure 7 The image shown is an AFM image of the template aperture layer at different focal lengths and tilt angles. It can be seen that when the half-cone angle φ is 10°... At 2°, the quantum dots fill the pores uniformly and densely with strong selectivity (i.e., there is little residue between the pores). When the pore tilt angle is below the lower limit of the optimal range, such as Figure 7 As shown, there are pinned three-phase lines at the orifice. Compared with Example 3, the quantum dot solution is more likely to form ring-shaped residues around the template orifice, increasing the residue between orifices. PL microscopy shows a decrease in inter-pixel contrast and a decrease in the uniformity of filling within the orifice.
[0054] The embodiments of the present invention enable the same fluorine-modified template / filling process to be rapidly adapted to different surface energies and solvent systems by means of geometric parameters, thereby forming a universal selective filling platform.
[0055] Example 5 like Figure 8 As shown, an electron transport layer (ZnO nanoparticle layer) and a top electrode (Al) were sequentially deposited on the nano-light-emitting layer obtained in Example 3, and then encapsulated to obtain a Nano-QLED device. The device structure is an inverted structure, and the fabrication process and device structure are as follows. Figure 8As shown, the microscopic images of the template aperture with a diameter of 300 nm and the electroluminescence (EL) micrographs of the Nano-QLED are as follows: Figure 9 As shown.
[0056] Example 6 Compared to Example 5, the difference is that, in addition to colloidal quantum dots, the fluorine-modified template with adjustable pore tilt angle and selective filling process of the present invention can also be used for: perovskite luminescent materials: a perovskite precursor solution is selectively filled into the template pores, followed by confined crystallization within the pores through low-temperature annealing at 100°C to form nanopixels, with ITO as the bottom electrode and ZnO as the perovskite crystal growth substrate. Figure 10 As shown.
[0057] Example 7 Compared with Example 5, the difference is that, in addition to colloidal quantum dots, the fluorine-modified template with adjustable pore tilt angle and selective filling process provided in this example can also be used for: OLED organic light-emitting materials / polymer light-emitting materials: selectively filling the template pores with a solution-processable organic light-emitting molecule solution to form nano-pixels, thereby preparing Nano-OLED, with ITO as the bottom electrode and PEDOT:PSS as the spin-coating substrate.
[0058] The above embodiments are only used to illustrate the principles and implementation of the present invention. Those skilled in the art can make various modifications or substitutions to the formula, structure, and process parameters without departing from the spirit of the present invention, and all such modifications or substitutions should fall within the protection scope of the present invention.
Claims
1. A fluorine-modified photoresist, characterized in that, The content of its components includes: 40–50 wt% phenolic epoxy acrylate Polydipentaerythritol pentaacrylate 10–20 wt% Fluorine-modified alkyl acrylates 5-15 wt% Photoresist solvent 15-35 wt% Free radical initiator 0.5-2 wt% Two-photon sensitizer 20–150 μM Triethylamine 0.1–1 wt% Anti-self-polymerizing agent 50–200 ppm.
2. The fluorine-modified photoresist according to claim 1, characterized in that, The fluorinated alkyl acrylate is a perfluoropolyether methacrylate, hexafluorobutyl methacrylate, or tridecylfluorooctyl methacrylate.
3. The fluorine-modified photoresist according to claim 1, characterized in that, The photoresist solvent includes one or more of hydrofluoroether, cyclopentanone, and γ-butyrolactone solvents.
4. The fluorine-modified photoresist according to claim 1, characterized in that, The free radical initiator is one or more of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 2,4-diethylthiazolidinone.
5. The fluorine-modified photoresist according to claim 1, characterized in that, The two-photon sensitizer is one or more of coumarin-102, 7-diethylamino-4-methylcoumarin, and eosin Y.
6. A method for preparing fluorine-modified photoresist according to any one of claims 1-5, characterized in that, include: (1) Prepare the ingredients according to the content of each component of the fluorine-modified photoresist, and then add phenolic epoxy acrylate, polydipentaerythritol pentaacrylate and fluorine-modified alkyl acrylate to the photoresist solvent and stir to obtain a mixed solution. (2) Add free radical initiator and two-photon sensitizer to the mixed solution until completely dissolved, then add triethylamine and anti-self-polymerization agent, and then vacuum degas and filter to obtain fluorine-modified photoresist.
7. The method for preparing fluorine-modified photoresist according to claim 6, characterized in that, The surface energy of the fluorine-modified template layer obtained after curing the fluorine-modified photoresist is less than 30 mN / m, and the water contact angle is greater than 100°.
8. A method for fabricating a Nano-LED device, characterized in that, include: (1) A first carrier transport layer is formed on the bottom electrode; (2) A patterned fluorine-modified template layer is obtained by spin-coating the fluorine-modified photoresist according to any one of claims 1-5 onto the first carrier transport layer, followed by exposure and development. The patterned fluorine-modified template layer has a plurality of nanopores arranged in an array. The inlet of the nanopores has a conical flared structure, and the capillary pressure ΔP at the inlet of the nanopores is... entry = 2γ·cos(θ eff ) / r entry , θ eff = θ F – α, and ΔP entry > 0, γ is the surface tension of the filling liquid, r entry Let θ be the equivalent radius of the hole inlet. eff To account for the effective contact angle after considering the additional hole inclination angle, θ F The intrinsic contact angle is α, where α is the angle of inclination of the pore axis of the nanopore relative to the normal of the template layer. (3) Add or spin-coat a luminescent material solution to the patterned fluorine-modified template layer, so that the luminescent material selectively fills into the nanopores under the drive of the inlet capillary pressure, and removes the residue between the pores during the spin-coating dewetting process to obtain a nano luminescent layer; (4) A second carrier transport layer and a top electrode are sequentially deposited on the nano-light-emitting layer and then encapsulated to obtain a Nano-LED device.
9. The method for fabricating a Nano-LED device according to claim 8, characterized in that, The semi-cone angle φ is 8°-12°.
10. The method for fabricating a Nano-LED device according to claim 8, characterized in that, The array formed by multiple nanopores has a pixel aperture of 300–500 nm, a pixel period of 600–1000 nm, and a pixel density of 25,400–42,333 PPI.
Citation Information
Patent Citations
Photoresist, quantum dot layer patterning method, quantum light-emitting diode (QLED), quantum dot color film and display device
CN105098002A
Quantum dot photoresist, quantum dot light-emitting layer obtained from quantum dot photoresist, QLED containing quantum dot light-emitting layer and preparation and application of QLED
CN112051709A